Physiological disproportions between un-corrected vision and degree of myopia - Gupta, Y; Rizvi, SAR; Gupta, M (Nepalese Journal of Ophthalmology, 2010)
Introduction: Anomalies of the refractive state of the eye are the commonest cause of defective vision. Purpose: To study the relationship between uncorrected visual acuity and refractive error in myopia in children, the prevalence of disparity between them and to find out the possible explanation for it. Materials and methods: 100 eyes of 50 myopic children were studied and analyzed to study relationship between the uncorrected visual acuity (UCVA) and its refractive status. 42 cases were chosen to study disparity, either in the form of uncorrected visual acuity or refractive error. To study these disparities, Keratometery for anterior corneal curvature and A-scan for axial length and anterior chamber depth were also done. Statistics: The results were analyzed statistically using student t-test while the relationship between uncorrected visual acuity (UCVA) and refractive error in myopia was obtained with Spearman's correlation coefficient (R). Results: The strength of association of uncorrected visual acuity and myopia as indicated by the correlation coefficient (0.897, p < 0.001) is a significant one. Out of 42 cases taken to study disparity, 24 (57 %) cases showed discrepancy either in the form of uncorrected visual acuity or refractive error. The reason for this disparity as proven statistically in our study is increased axial length (p value< 0.001). Conclusions: There exists a linear relationship between UCVA and myopia, yet an accurate prediction of uncorrected visual acuity cannot be made on the basis of the refractive error or vice-versa for any single individual, as there exists a disparity either in form of UCVA or refractive error in myopia. Keywords: refractive error; myopia; uncorrected visual acuity; disparity; axial length DOI: 10.3126/nepjoph.v2i2.3721 Nep J Oph 2010;2(2) 138-144